2022
DOI: 10.1186/s13020-022-00654-z
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Chinese medicine for COVID-19 rehabilitation: a multicenter observational study

Abstract: Objectives This study aimed to evaluate the effects of Chinese Medicine (CM) on the health condition of the post-COVID-19 patients, particularly with the CM Syndrome diagnosis and Body Constitutions (BC), as well as related clinical characteristics. Methods 150 participants who had COVID-19 and discharged from Hong Kong public hospitals were recruited. They were provided with three to six months of CM treatments, during which assessments were made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors would like to make corrections after identifying the errors below which were caused by typo mistakes and the latest update of data analysis prior to publication but updating on some texts and Fig. 6A correspondingly had been missed.…”
Section: Correction: Chinese Medicine (2022) 17:99 Https://...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors would like to make corrections after identifying the errors below which were caused by typo mistakes and the latest update of data analysis prior to publication but updating on some texts and Fig. 6A correspondingly had been missed.…”
Section: Correction: Chinese Medicine (2022) 17:99 Https://...mentioning
confidence: 99%
“…1186/ s13020-022-00654-z. *Correspondence: ldzhong@hkbu.edu.hk; bzxiang@hkbu.edu.hk 1 School of Chinese Medicine, Hong Kong Baptist University, Hong Kong, China Full list of author information is available at the end of the article Corrected version: The statement "However, with each increased age year, the score obtained in LFQ will decrease by 0.11" has been removed.…”
Section: Chinese Medicinementioning
confidence: 99%
“…To date, there are very few clinical studies of using TCM to treat the residual symptoms of COVID-19 recovered patients. A multi-center observational study in Hong Kong has shown that individualized TCM treatments could facilitate resolution of clinical symptoms (including fatigue, cough, shortness of breath, post-meal fullness, and loose stool), improve lung functions, and lead to healthier CM body constitutions in COVID recovered patients ( 21 ). A randomized controlled trial comparing a Chinese medicine (Qingjin Yiqi granules) combined with standard rehabilitation treatments (SRTs) against SRTs alone has also shown that the CM granules could assist reduction in fatigue and breathlessness ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,5–7] Recently, it has been used to evaluate the treatment effects of Chinese medicine on COVID-19 rehabilitation. [8]…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,[5][6][7] Recently, it has been used to evaluate the treatment effects of Chinese medicine on COVID-19 rehabilitation. [8] In the CCMQ, body constitution is categorized into 1 balanced type and 8 unbalanced types (yang-deficiency, yin-deficiency, qi-deficiency, phlegm dampness, heat dampness, blood stasis, qi-stagnation, and inherited special). [1] A balanced constitution is a non-symptomatic or healthy type, whereas unbalanced types are in a suboptimal health state and are more susceptible to certain pathogenic factors and related diseases.…”
Section: Introductionmentioning
confidence: 99%